Detailed exam of the exclusion of company law in the Rome I Regulation to the thread of the Verein für konsumenteninformation case: legal strength towards the investor consumer - Carrizo Aguado, David (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The guardianship of consumers within the scope of Regulation (EC) 593/2008 is based on two pillars: on the one hand, the conditions and limits of the autonomy of the will in the choice of applicable law and, on the other, the determination of when a provision of services is carried out exclusively in a State other than that of the habitual residence of the consumer for the purpose of excluding said contract from the protection granted by article 6 of the said norm. The study revolves around offering a reasoning for the exclusion of the scope of material application of Regulation (EC) 593/2008 in relation to a fiduciary contract whose purpose is the administration of a participation in a limited partnership. Operations such as ale or trust related to social interests may raise issues pertaining to company law, but the same does not occur with the contracts underlying those operations. In particular, the mere circumstance that a contract has a link with “matters pertaining to company law” does not have the effect of removing from the material perimeter of Regulation (EC) 593/2008 those obligations that have their origin in that contract.
Keywords: International company law; applicable law; abusive clauses; distance contracting; cross-border consumer contract